Stance-marking of interaction in research articles written by non-native speakers of English: An analytical study - Al-Zubeiry, Hameed Yahya A; Assaggaf, Hussein Taha (Studies in English Language and Education, 2023)
Stance-marking of interaction is considered an important element for achieving effective communication in any academic discourse. Based on a descriptive-analytic approach, the present study addresses a two-fold objective: a) analyzing and comparing stance-marking of interaction across disciplines in the research articles written by Arab non-native speakers of English, and b) describing how researchers lack of using interactional linguistic markers in their research articles would constrain readers from interacting with the arguments and opinions they expressed in their academic articles. The corpus data comprised forty research articles selected randomly from two disciplines: sciences (ten engineering and ten medicine) and humanities (ten education and ten applied linguistics). The findings of the study showed an evident lack of stance-marking in research articles written in English by Arab researchers. A total of 307 occurrences of lack of stance markers were detected in the study corpus. Arab non-native researchers deficiency in employing stance markers in their research articles is likely to be attributed to their lack of knowledge and awareness about the effectiveness of stance-marking of interaction in academic writing. The results also show that science discipline articles have a higher frequency of lack of stance markers than humanities discipline articles. The difference between the two disciplines could be attributed to the distinctive persuasive nature of each discipline. The study concluded with some recommendations, including the inclusion of stance-marking of interaction in evaluating papers for publication and teaching academic writing to Arab non-native English postgraduate students.